Forecasting euro area recessions in real-time - Inske Pirschel (Kiel Institute for the World Economy (IfW), 2016)
I present evidence that the linear mixed-frequency Bayesian VAR provides very sharp and well calibrated monthly real-time recession probabilities for the euro area for the period from 2004 until 2013. The model outperforms not only the univariate regime-switching models for a number of hard and soft economic indicators and their optimal linear combinations, but also a real-time recession index obtained with Google Trends data. This result holds irrespective of whether the joint predictive distribution of several economic indicators or the marginal distribution of real GDP growth is evaluated to extract the real-time recession probabilities of the mixed-frequency Bayesian VAR. The inclusion of the confidence index in industry turns out to be crucial for the performance of the model.
Keywords: C53; E32; E37; 330; Density nowcasting; Real-time recession forecasting; Mixed-frequency data; Bayesian VAR; Regime-switching models; Linear opinion pool; Google Trends